Polyphenol Content in Chinese Bee Products and Their Antioxidant Activity - Dai, Yun; Ding, Zhongjuan; Lei, Yu; Yufen, Bi (Asian Journal of Chemistry, 2013)
Considering gallic acid as the standard, a spectroscopic method is established for the determination of the polyphenol contents in bee products (6 kinds of propolis capsules, 3 kinds propolis tablets and 12 kinds bee pollen). The scavenging capacity of samples to DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals was studied. The results show that the average content of polyphenol in capsule is 30.49 %, in tablet is 27.01 %, in bee pollen is 3.67 %; the removing ability to DPPH free radicals of propolis capsule and its tablet are stronger than bee pollens, there is obvious linear relationship between the total polyphenol content and its ability of scavenging free radicals in certain concentration.